2012
DOI: 10.3892/ol.2012.636
|View full text |Cite
|
Sign up to set email alerts
|

Teratoma showing the features of retinal structure: A case of sacrococcygeal teratoma

Abstract: Abstract. Teratoma is a tumor that forms triploblastic tissues and the common sites of occurrence are sacrococcygeal lesions and the ovaries. The majority of cases are curable with surgical resection and the prognosis depends on the extent and histological scoring of the tumor. In the present study, we report a case of sacrococcygeal teratoma of a newborn showing features of a retina-like structure. A 29-year-old woman gave birth prematurely to an infant girl with sacrococcygeal teratoma. Surgical resection wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…26 The presence of retinal pigmented epithelium in hESCderived islet implants has not been reported previously, although retinal-like tissue in teratomas has been reported in a few case studies. 27,28 With the absence of teratomas in the intermediate differentiated groups but where retinal pigmented epithelium developed in one animal after 26 weeks, we need an alternative explanation for the finding. The retina is derived from the optic neuroepithelium which develops from the anterior neuroectoderm, 29 whereas hESC-derived islet protocols are optimized for endoderm-lineage pancreatic development and thus a different germ layer.…”
Section: Discussionmentioning
confidence: 99%
“…26 The presence of retinal pigmented epithelium in hESCderived islet implants has not been reported previously, although retinal-like tissue in teratomas has been reported in a few case studies. 27,28 With the absence of teratomas in the intermediate differentiated groups but where retinal pigmented epithelium developed in one animal after 26 weeks, we need an alternative explanation for the finding. The retina is derived from the optic neuroepithelium which develops from the anterior neuroectoderm, 29 whereas hESC-derived islet protocols are optimized for endoderm-lineage pancreatic development and thus a different germ layer.…”
Section: Discussionmentioning
confidence: 99%
“…Sergi et al [12] and Takamatsu et al [13] reported a fetal sacrococcygeal teratomas with the development of a completely formed eye in the former, and retina-like structure with immature neural components of true rosettes and primitive neural tubes in the latter. They pointed the importance of blood supply and high oxygen concentration for the formation of rods and cones based on their hypothesis that these factors are important in the differentiation of the cells.…”
Section: Discussionmentioning
confidence: 99%
“…In 1999, Sergi et al published one case with a histopathologically confirmed optical component within a completely formed eye in fetal sacrococcygeal teratoma . Furthermore, in 2012 Takamatsu et al presented a similar case of sacrococcygeal teratoma with retina‐like structures in a newborn . The majority of data on immature teratoma today is gained from extracranial tumors.…”
Section: Discussionmentioning
confidence: 99%
“…15 Furthermore, in 2012 Takamatsu et al presented a similar case of sacrococcygeal teratoma with retina-like structures in a newborn. 16 The majority of data on immature teratoma today is gained from extracranial tumors. More reports and examinations of intracranial cases are needed to extend our understanding of this unique CNS tumor group.…”
Section: Discussionmentioning
confidence: 99%